Baseline amyloid and tau PET imaging characteristics in the ongoing phase 2 study of tilavonemab in early Alzheimer's disease. (1st February 2022) - Wooten, Dustin W.; Guo, Qi; Jin, Ziyi; Gladstein, Scott; Stage, Edwin; Hesterman, Jacob; Fisseha, Nahome; Florian, Hana; Comley, Robert A.
Abstract: Background: Amyloid and tau are recognized hallmarks of Alzheimer's disease (AD). Tilavonemab is a monoclonal antibody that binds to the N terminus of human tau and is being developed as a treatment for early AD. The goal of this work is to present the baseline amyloid and tau PET imaging characteristics of patients enrolled in the ongoing phase 2 study of tilavonemab. Method: 453 patients who met the clinical criteria for early AD and had a positive amyloid PET scan (by visual read) at screening were randomized into the study. Amyloid PET was quantified on the standard Centiloid (CL) scale utilizing a processing pipeline developed in‐house and validated using recommended procedures [Klunk, et al., 2015]. Tau PET imaging using 18 F‐MK6240 was also performed in a subset of patients to assess presence of tau pathology, the target of tilavonemab, and to monitor disease progression and treatment effects. Here we report baseline tau PET data from 59 subjects randomized into the trial (out of 70 scans collected, not including screen fails or out of baseline window scans). Tau PET was quantified in Braak regions I‐VI using standardized uptake value ratio (SUVR), extent (percentage of voxels within a region above threshold) and load (extent * mean SUVR of voxels within a region above threshold) metrics. Ventral cerebellar gray matter was used as a reference region for SUVR calculation and to determine the subject‐specific threshold needed for the extent and load calculation. Result: Over 99% of subjects (449/453) had amyloid measurements greater than 20CL, a threshold used for positivity [Burnham, et al., 2020], consistent with visual read; mean±s.d. was 99.0±31.1 CL. For the 59 patients with baseline tau PET data 95% (56/59) were considered to have elevated tau pathology in the brain (SUVR ≥1.27 in the entorhinal cortex [Betthauser, et al., 2020]). The tau metrics for Braak regions I‐VI are summarized in Table 1. Conclusion: This analysis confirmed the presence of amyloid pathology in the patients randomized into the trial and suggested a high proportion of patients have tau pathology in the brain. Future analyses will examine how tilavonemab effects tau pathology.